THE IMPORTANCE OF SOCIAL PERSONAL DEVELOPMENT STUDENTS - Nur Amalina, Nyayu; Oktasari, Resti; AR, Silvia (IKIP Siliwangi, 2024)
Personal social development is very important considering the challenges students face, such as bullying and socializing unhealthily. This research focuses on the need to create a safe and supportive learning environment to support the growth of students' character. The purpose of this study is to explore the importance of social personal development and formulate an effective mentoring program. The method used was a qualitative approach with in-depth interviews and observations of fifteen students, which aimed to understand their experiences regarding bullying and social support at school. The results showed that a large part of the students once experienced or witnessed bullying behavior, which negatively impacted their mental health and concentration in learning. Proposed mentoring programs have personal-social goals To raise students' awareness of the dangers of bullying, build social skills, and create positive relationships with peers. This research emphasizes the importance of collaboration between schools, parents, and the community in supporting the social development of private students, so that it is expected to form a young generation who are not only intelligent in terms of academics, but also have good character and are able to interact in a positive way in public.